HEAT TREATMENT METHOD FOR THE PREVENTION OF CHANGE IN DIMENSION OF MOLD ACCORDING TO THE FLOW OF TIME DUE TO THE MINIMIZE OF RETAINED AUSTENITE AND TRANSFORMATION SUPPRESSION OF RETAINED AUSTENITE STRUCTURE TO MARTENSITE AND STABILIZATION OF RETAINED AUSTENITE OF HIGH C-HIGH CR-(V) TYPE TOOL STEEL - YOON, SANG KI; NAM, KUNG CHUL; YOON, YONG DON (2014)
The purpose of the present invention is to perform three-staged cryogenic cooling in order to prevent the dimension of a product produced in a mold from being changed or prevent the problem in which the precision of precision machine parts is reduced because the dimension is changed as time passes in the case of a precision mold and the precision machine parts used in semiconductors, electronics, and etc. or in order to minimize it by maximally transforming residual austenite tissues, which cause the dimensional change by remaining in a tool steel for the mold, after quenching heat treatment to martensitic tissues. Furthermore, the residual austenite tissues remaining in an unstable state are subsequently transformed to the martensitic tissues to be minimized even after the quenching and three-staged cryogenic cooling. The tempering heat treatment is performed for removing internal stress and giving stability to heat. The residual austenite tissues are suppressed so that the residual austenite tissues are transformed to the martensitic tissues to prevent dimensional change (strain aging, aecular change) as the unstable residual austenite tissues remaining after tempering are transformed to the martensitic tissues as the time passes. The residual austenite tissues remain in a stable state. The dimensional change of the precision mold and abrasion of precision machine parts due to the passing of time can be maximally suppressed and be minimized to allow the residual austenite tissues to remain in a stable state.